2013
DOI: 10.35790/ecl.1.2.2013.3280
|View full text |Cite
|
Sign up to set email alerts
|

Rinitis Alergi Di Poliklinik THT-Kl Blu Rsu Prof. Dr. R. D. Kandou Manado Periode Januari 2010 – Desember 2012

Abstract: Allergic Rhinitis is an atopic condition which most often occurred. The incidence of allergic rhinitis is estimated at about 10% of the general population. This study aims to know the profile of allergic rhinitis patients in Ear, Nose and Throat – Head and Neck Surgery Department at Prof. Dr. R. D. Kandou General Hospital, Manado period January 2010 – December 2012 by using descriptive retrospective study method. The overall number of objects in this study are 209 patients. The result, distribution by year obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…9 In accordance with the results of the study by Reinhard, Palandeng, Pelealu (2013) which was obtained from patients in the ENT-HN outclinic of Prof. Dr. R. D. Kandou General Rospital, Manado, the most frequent symptoms was sneezing with 119 patients (39.40%), rhinore with 108 patients (35.76%), nasal congestion with 75 patients (24.83%). 10 The results of this study showed that allergic rhinitis patients accompanied with watery eye (rhinoconjunctivitis) with 73.8%, which is in accordance to the study of Ologe et al (2013) which stated that rhinoconjunctivitis occurred in 75 patients with allergic rhinitis (92.6%). 16 Watery nose, sneezing, nasal congestion with lacrimation, and itchy nasal mucosa, conjunctiva and oropharynx are the classic features of allergic rhinitis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…9 In accordance with the results of the study by Reinhard, Palandeng, Pelealu (2013) which was obtained from patients in the ENT-HN outclinic of Prof. Dr. R. D. Kandou General Rospital, Manado, the most frequent symptoms was sneezing with 119 patients (39.40%), rhinore with 108 patients (35.76%), nasal congestion with 75 patients (24.83%). 10 The results of this study showed that allergic rhinitis patients accompanied with watery eye (rhinoconjunctivitis) with 73.8%, which is in accordance to the study of Ologe et al (2013) which stated that rhinoconjunctivitis occurred in 75 patients with allergic rhinitis (92.6%). 16 Watery nose, sneezing, nasal congestion with lacrimation, and itchy nasal mucosa, conjunctiva and oropharynx are the classic features of allergic rhinitis.…”
Section: Discussionsupporting
confidence: 91%
“…In their study, the most frequent age group with allergic rhinitis was the 21-30 years old with 50 (23.92%) cases. 10 While on the study by Denny Satria Utama (2010), the most frequent was the 18-35 years old (44.6%), <18 years old (28.4%), 36-50 years old (24.3%), and>50 years old (2.7%). 11 The result of study conducted by Rahmawati, Suprihati, Muyassaroh (2011) found that 68 patients with persistent allergic rhinitis has an average age of 27.8±11.7 years, while the youngestwas 11 years old and the oldest was 54 years old, the most frequent age group was 23-34 years old (38.2%).…”
Section: Discussionmentioning
confidence: 96%
“…Pada tahun 2013 terdapat 1.018 kasus rinitis alergi di RSUD Dr. Soetomo Surabaya dan meningkat 10 sampai 20 kasus setiap bulannya, sedangkan data RSUD Dr. Saiful Anwar Malang terdapat 132 kasus baru sepanjang tahun 2015 (Hartini, 2016). Reinhard et al (2013) menyatakan bahwa prevalensi rinitis alergi tertinggi berada pada kelompok usia 21-30 tahun.…”
Section: Pendahuluanunclassified
“…11 Menurut hasil riset Reinhard et al (2012), berdasarkan jenis pekerjaan yang paling sering terkena rinitis alergi adalah pegawai yaitu sebesar 34,93%. 12 Rinitis alergi merupakan salah satu faktor penyebab terjadinya penurunanan produktivitas kerja dan terjadi kerugian secara finansial. 13 Namun masih sedikit penelitian yang membahas tentang kejadian rinitis alergi dan hubungannya dengan kualitas hidup pegawai khususnya guru.…”
unclassified